Smart Monitoring and Warning Landslide System using Internet of Things - Azlina Idris, Mohamed Ahmed Hafez, Norbaya Sidek, Warid Wazien Ahmad Zailani, Nur Anis Zulaikha Mohd Baharuddin (Mathematical Statistician and Engineering Applications, 2022)
A landslide is a natural disaster that will damage social life. Currently, the established monitoring system for the landslide is not very efficient as no system uses a component that can detect rainfall, seeing that Malaysia is a tropical country with high rainfall intensity. This research aims to design a smart monitoring and warning system to detect the occurrence of landslides in real-time. The system will be proposed at Bukit Bauk Dungun, which is the only place for hiking trails, so the rainfall sensor is a suitable sensor that can alert and give an early sign to people because most people are coming from a different place. Three sensors, rainfall, vibration and soil moisture sensor, are connected to NodeMCU (ESP8266). When the data is collected, it will send an alert to the end-user using cloud Blynk via mobile phone. The result obtained based on the sand and soil shows that the soil sample is highly triggered to landslide because the reading of sensor at the soil for rain sensor is quickly high with 71% and reading sensor of soil moisture is 90% so that there will have a movement of the land. Therefore, this proposed system will get a more accurate value that will be easier to user monitor the condition of land triggered by a landslide.